The Influence of Employee Engagement, Workload, and Work Environment on Employee Productivity at PT. Surya Steel Surabaya - Syalaisa Amani Fatihah; Acep Samsudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research aims to determine and analyze the effect of Employee Engagement, Workload, and Work Environment on Employee Productivity at PT. Surya Steel Surabaya. This research method is quantitative with an associative research type. The number of samples in this research was 42 employees in the production department, with data collection carried out by means of observation, interviews, direct questionnaires, and literature study, and data processing carried out with the help of the SPSS 30 program. Sampling used saturated sampling techniques and data analysis techniques using multiple linear regression analysis. The results of this study indicate that Employee Engagement, Workload, and Work Environment simultaneously have a significant positive effect on Employee Productivity at PT. Surya Steel Surabaya. Partial testing of Employee Engagement and Work Environment has a significant positive effect on Employee Productivity. While the Workload variable has an insignificant effect on Employee Productivity. With these factors, the company can implement more effective policies to increase employee productivity at PT. Surya Steel Surabaya. This research provides theoretical implications in increasing knowledge related to the relationship between variables, as well as practical implications for companies in increasing employee productivity.